High-flow nasal oxygen vs. conventional oxygen therapy in patients with COVID-19 related acute hypoxemic respiratory failure and a do not intubate order: a multicentre cohort study - Daphne J. T. Sjauw; Lisa M. Hessels; Marieke L. Duiverman; Judith Elshof; Matthijs L. Janssen; Yasemin Türk; Leo Heunks; Sara J. Baart; Evert-Jan Wils; Dutch HFNO study group; NORMO2 project group (Respiratory Research)
Abstract Background High-flow nasal oxygen (HFNO) is frequently used to treat patients with acute hypoxemic respiratory failure (AHRF) due to viral pneumonia, including COVID-19. However, its clinical effect compared to conventional oxygen therapy (COT) remains largely unexplored in patients with a do not intubate (DNI) order. We aimed to assess whether HFNO compared to COT is associated with improved clinical outcomes in hospitalized patients with AHRF due to COVID-19 and a DNI order. Methods This analysis included patients with a DNI order and SARS-CoV-2 infection, selected from three observational studies, who were treated with COT only or HFNO. The primary endpoint was in-hospital mortality, the secondary endpoint was hospital length of stay (LOS). The effect of HFNO vs. COT was assessed using multivariable regression, accounting for pre-selected confounders. Results Between March 2020 and September 2021, 116 patients received HFNO and 110 patients received COT. Median age was 78 [72–83], and 78% of the patients had a Clinical Frailty Scale score of 4 to 9. In-hospital mortality was 64% for HFNO and 71% for COT (p = 0.29), with an adjusted odds ratio of 0.72 (95% confidence interval [0.34–1.54], p = 0.40). Hospital LOS was 11 [6–18] days for HFNO, and 7 [4–12] days for COT (p < 0.001), with a remaining difference after adjusting for confounders (p < 0.01). Conclusion The lack of survival benefit and increased hospital LOS should be taken into account when considering HFNO for patients with a DNI order, suffering from AHRF due to viral pneumonia, like COVID-19. Clinical trial registration HFNO-COVID-19 study: DTR, NL9067 (Dutch Trial Registry), registration date: 27-11-2020.